The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1590/s1984-46702011000400002
|View full text |Cite
|
Sign up to set email alerts
|

A molecular method to detect and identify the native species of southwestern Atlantic Crassostrea (Mollusca: Ostreidae)

Abstract: Among oysters, species of Crassostrea (Sacco, 1897) are the most attractive to aquaculture. In Brazil, the genus is represented by C. rhizophorae (Guilding, 1828) and C. brasiliana (Lamarck, 1819). Because the maturation and breeding technology is not well developed for these species, aquaculturists need a reliable method to decide the correct time to place spat collectors in the field, and to identify both species, which are morphologically similar. In this study a specific Multiplex PCR protocol was develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Oysters used in this research were identified initially by morphological characteristics and by the position they occupy in the water column, as described by Castilho-Westphal (2012). This preliminary identification was confirmed by sampling (n = 263) and further application of molecular protocols developed by Ludwig et al (2011). Of these, 59% belonged to the C. brasiliana species, 38% belonged to C. rhizophorae, and 3% were classified as Crassostrea sp.…”
Section: Species Identificationmentioning
confidence: 64%
See 2 more Smart Citations
“…Oysters used in this research were identified initially by morphological characteristics and by the position they occupy in the water column, as described by Castilho-Westphal (2012). This preliminary identification was confirmed by sampling (n = 263) and further application of molecular protocols developed by Ludwig et al (2011). Of these, 59% belonged to the C. brasiliana species, 38% belonged to C. rhizophorae, and 3% were classified as Crassostrea sp.…”
Section: Species Identificationmentioning
confidence: 64%
“…This preliminary identification was confirmed by sampling ( n = 263) and further application of molecular protocols developed by Ludwig et al . (). Of these, 59% belonged to the C. brasiliana s pecies, 38% belonged to C. rhizophorae , and 3% were classified as Crassostrea sp.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Multiplex PCR techniques have been developed specifically for the identification of oysters of the genus Crassostrea (LUDWIG et al, 2011;MELO et al, 2013), with the objective of optimizing the taxonomic identification of these organisms, providing an important tool for aquaculture and fishery operations. In addition to this approach, a fragment of approximately 650 base pairs of the 5' extremity of the mitochondrial Cytochrome oxidase subunit I (COI) gene has been adopted as a universal identification system for animal species, including the oysters of the Atlantic Ocean.…”
Section: Introductionmentioning
confidence: 99%